Influência da nicotina na expressão gênica de HIF-1α, PI3K, AKT, ERK1/2 e CA-IX em linhagens celulares SCC9 e DOK - Santos, Joaquim Gasparini dos (2017)
Oral cavity squamous cell carcinoma (oral SCC) is the most common type of malignancy that affects an oral cavity, usually driven by the pre-malignant lesions, such as leukoplakia. Smoking is one of the main risk factors for oral SCC. Nicotine is the major natural compound present in tobacco, studies have pointed out that its binding to Nicotinic Acetylcholine Receptors (nAChRs) leads to an increase in the production of Reactive Oxygen Species (ROS) and of growth factors that bind to Receptor Tyrosine Kinase (RTK) triggering the activation of MAPKs and Phosphatidylinositol-3-kinase (PI3K / Akt), culminating in the activation of the HIF-1α protein and CA-IX expression, leading to increased cell proliferation, migration, metastasis and inhibition of tumor cell apoptosis. For this purpose we evaluated the expression of genes ERK1 / 2, PI3K, AKT, HIF-1α and CA-IX in cell culture and SCC9 DOK exposed to different concentrations of nicotine and hypoxia chamber at various times. The effect of increasing concentrations of nicotine and exposure to hypoxia chamber in cell lines of DOK and SCC9, cell viability and expression of the genes in question were performed using the MTS technique and Real Time. The results showed higher expression of HIF-1α, PI3K, AKT, ERK1 / 2 and CA-IX in SCC9 at 24 hours in cultivars with 0.1 mM nicotine concentration when compared to control. Comparing the expression of nicotine concentrations with cultured cells in a hypoxia chamber, a greater 24 h time expression in 0.1 mM of HIF-1α, PI3K, AKT and ERK1 / 2 genes was noted, whereas CA-IX was a low expression of hypoxia chamber. The DOK results show that nicotine causes a small increase over control in the expression of HIF-1a in 5 mM, AKT in 2.5 mM and ERK1 in 0.1 mM in the time of 8 hours, during the 24 hours observed a small increase in ERK2 at 2 mM concentration. Compared hypoxia chamber with the control other concentrations and nicotine, it was observed that only in HIF-1α the expression was lower in the time of 8 hours, but in 24 hours this expression exceeded the expression in the control and in the nicotine exposed cells. It is concluded that nicotine is able to modulate a higher expression of genes in question SCC9 than DOK.